Finding salvation in Christ: essays on Christology and soteriology in honor of William P. Loewe - Denny, Christopher D.; Loewe, William P. (Pickwick Publ., 2011)
William Loewe, Bernard Lonergan, and the salvific matrix / Christopher D. Denny -- Estote firmi : New York's local church under Cardinal Spellman's watch : some foundations for an intellectual journey / Patrick J. Hayes -- Jesus founding the church : a perspective drawing upon Loewe and Lonergan / Dennis M. Doyle -- Schillebeeckx's phenomenology of experience and resurrection faith / Anthony J. Godzieba -- Narrating slavation : historical Jesus research and soteriology / Christopher McMahon -- Injustice at Ephesus / Gerard S. Sloyan -- Propter nostram salutem : the cross and our salvation / Thomas J. Schärtl -- Anselm's Cur Deus homo? : genres of language and the narrative of salvation / Christopher D. Denny -- The law of the cross and emergent probability / Cynthia S.W. Crysdale -- Finding the ground : method, universality, and ethical discourse / David M. Hammond -- "Irrational exuberance" at the foot of the cross : redeeming the rhythms of economic life / Stephen L. Martin -- Woundedness and redemption in the feminine body of Christ / Kathleen A. McMannus -- Marriage practices and the redemption of the world / Jason E. King -- Christ in the many and diverse religions : an interreligious christology / Peter C. Phan -- Epilogue: Continuing conversations / William P. Loewe